2021
DOI: 10.1111/jar.12859
|View full text |Cite
|
Sign up to set email alerts
|

‘It's been adapted rather than impacted’: A qualitative evaluation of the impact of Covid‐19 restrictions on the positive behavioural support of people with an intellectual disability and/or autism

Abstract: Background We used a qualitative approach to explore the experiences of social care staff regarding the provision of positive behavioural support (PBS) to people with an intellectual disability at the height of the Covid‐19 restrictions. Method We conducted semi‐structured interviews with 19 staff who had recently completed a PBS workforce development programme. Data were analysed using thematic analysis. Results Three themes were identified … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 22 publications
1
17
0
1
Order By: Relevance
“…Data from research studies reflect concerns similar to those expressed in clinician opinion pieces. Over a 15‐month period, several studies explored the impacts of pandemic‐related closures and restrictions on the mental health and well‐being of people with ID from numerous countries, including Chile (Rosencrans et al, 2021 ), Italy (Zingale et al, 2020 ), South Korea (Kim et al, 2021 ), United Kingdom (Courtenay, 2020 ; Courtenay & Perera, 2020 ; McKenzie et al, 2021 ; Murray et al, 2021 ; Rawlings et al, 2021 ; Willner et al, 2020 ), United States (Jeste et al, 2020 ), Canada (Lake et al, 2021 ), Ireland (McCarron et al, 2020 ; McCausland et al, 2021 ), France (Nollace et al, 2020 ), Spain (Amor et al, 2021 ; Navas, Amor, et al, 2021 ), Netherlands (Embregts et al, 2020 ; Scheffers et al, 2021 ; Schuengel et al, 2020 ; Zaagsma et al, 2020 ), and Israel (Araten‐Bergman & Shpigelman, 2021 ). To date, there has been a prominent focus on the challenges experienced by children and youth with ID and their families as a result of pandemic response plans, such as the transition of in‐person learning to virtual education.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Data from research studies reflect concerns similar to those expressed in clinician opinion pieces. Over a 15‐month period, several studies explored the impacts of pandemic‐related closures and restrictions on the mental health and well‐being of people with ID from numerous countries, including Chile (Rosencrans et al, 2021 ), Italy (Zingale et al, 2020 ), South Korea (Kim et al, 2021 ), United Kingdom (Courtenay, 2020 ; Courtenay & Perera, 2020 ; McKenzie et al, 2021 ; Murray et al, 2021 ; Rawlings et al, 2021 ; Willner et al, 2020 ), United States (Jeste et al, 2020 ), Canada (Lake et al, 2021 ), Ireland (McCarron et al, 2020 ; McCausland et al, 2021 ), France (Nollace et al, 2020 ), Spain (Amor et al, 2021 ; Navas, Amor, et al, 2021 ), Netherlands (Embregts et al, 2020 ; Scheffers et al, 2021 ; Schuengel et al, 2020 ; Zaagsma et al, 2020 ), and Israel (Araten‐Bergman & Shpigelman, 2021 ). To date, there has been a prominent focus on the challenges experienced by children and youth with ID and their families as a result of pandemic response plans, such as the transition of in‐person learning to virtual education.…”
Section: Methodsmentioning
confidence: 99%
“…Adults in the Netherlands who received video conferencing training prepandemic reported that remote online support was useful during the pandemic (Zaagsma et al, 2020 ). Similarly, a qualitative study of providers trying to deliver positive behavior supports during the first wave noted that online supports seemed helpful to individuals when home‐based care was not permitted (McKenzie et al, 2021 ).…”
Section: Methodsmentioning
confidence: 99%
“…The impact and potential for distress of DSPs cannot be underestimated: within these adjusted roles, however, there were also positive impacts; increased time spent by staff with the people themselves provided improved, longitudinal opportunities to learn more about them. McKenzie et al’s ( 2021 ) study focused on adaptation in the implementation of positive behaviour support (PBS) during lockdown restrictions. Staff learned about the PBS principles and how to apply them within the changing context, while simultaneously seeking to maintain routine and sameness thereby reducing distress for all concerned (McKenzie et al, 2021 ; Murray et al, 2021 ).…”
Section: Resultsmentioning
confidence: 99%
“…McKenzie et al’s ( 2021 ) study focused on adaptation in the implementation of positive behaviour support (PBS) during lockdown restrictions. Staff learned about the PBS principles and how to apply them within the changing context, while simultaneously seeking to maintain routine and sameness thereby reducing distress for all concerned (McKenzie et al, 2021 ; Murray et al, 2021 ). Anecdotally, changing routines and rhythms have been reported as possibly reducing incidences of behaviours that challenge in some cases.…”
Section: Resultsmentioning
confidence: 99%
“…Ett exempel är ökade svårigheter att vidmakthålla arbetssätt under restriktionerna vilket bedömdes försvåra tillvaron för en del personer med IF. Samtidigt pekar en engelsk studie på att pandemin medfört en mer avgränsad och lugn miljö vilket en del personer med IF troligen mått bättre av (McKenzie, Murray & Martin 2021). Nederländsk personal har under pandemin försökt hitta nya vägar att hålla kontakt med personer med IF när fysiska möten måste begränsas eller undvikas och börjat erbjuda stöd digitalt för att stärka personernas resiliens (Scheffers, Moonen & van Vugt 2021).…”
Section: Syfte Och Frågeställningarunclassified